Breast Cancer Patients Survival and Associated Factors: Reported Outcomes from the Southern Cancer Registry in Portugal - André, Maria do Rosario (2014)
Objectives: Although the breast cancer incidence in Portugal is lower than the European average, it is the most frequent cancer in women. Overall, mortality rates are heterogeneous throughout Portugal. Implicated factors may include demographic and socioeconomic aspects, tumor biological characteristics, and access to medical care. The aim of this study is to detect survival differences in female breast cancer and identify the main associated factors.Material and Methods: We have conducted a population-based, retrospective cohort study with follow-up. Incident breast cancer cases diagnosed in 2005 of residents in the southern region of Portugal were included. Data was collected from the Southern Portugal Cancer Registry (ROR-Sul) database and completed with clinical chart information.Results: A total of 1 354 patients were included in this study. Observed geographical variations were as follows: for age distribution, with an aging population in Alentejo; for tumor sub-types, there was a higher incidence of HER2-positive tumors in the Algarve and a higher incidence of HER2-negative tumors in Região Autónoma da Madeira. Reported estimated 5-year overall survival was 80%, with significant association with tumor stage, hormone receptor and HER2 status. No survival differences were identified among women from distinct geographical regions.Discussion: Although we found differences in age and tumor sub-type distribution between geographical regions, our study does not support the existence of discrepancies in breast cancer survival between these regions. Tumor biological characteristics seem to be the main associated factor with breast cancer survival in our population.Conclusions: Our study confirms the association between patient survival and tumor stage, hormone receptor and HER2 status. However, no differences in patient survival were observed among different regions of residence.Keywords: Breast Neoplasms; Neoplasm Staging; Survival Analysis; Portugal.